Mechanical parameters of the squeeze film curvilinear bearing lubricated with a Prandtl fluid - Walicka, Anna; Walicki, Edward (Zielona Góra: Uniwersytet Zielonogórski)
Based upon a Prandtl fluid flow model, a curvilinear squeeze film bearing is considered. The equations of motion are given in a specific coordinate system. After general considerations on the Prandtl fluid flow these equations are used to derive the Reynolds equation. The solution of this equation is obtained by a method of successive approximation. As a result one obtains formulae expressing the pressure distribution and load-carrying capacity. The numerical examples of the Prandtl fluid flow in gaps of two simple bearings are presented.
Keywords: modified Reynolds equation; Prandtl fluid; squeeze film; mechanical parameters of bearing; additives